Role of Halogen F---H Bonds in Potassium Trifluoroborate Salts - Iramain, Maximiliano Alberto (2019)
In this work, the role of halogen F---H bonds in potassium 3-furoyl-trifluoroborate (FTFB), 2-isonicotinoyl-trifluoroborate (ITFB), 5-hydroxypentanoyl-trifluoroborate (HTFB), 5-Br-2-isonicotinoyl-trifluoroborate (Br-ITFB), 6-chloro-2-isonicotinoyl-trifluoroborate (Cl-ITFB), 4-fluorobenzoyl-trifluoroborate (FBTFB) and 2-phenylacetyl-trifluoroborate (PTFB) salts have been studied in gas phase and in aqueous solution by using NBO and AIM calculations with the hybrid B3LYP/6-311++G** method and the SCRF and SM models. In addition, the corrected solvation energy by using ZPVE and non electrostatic terms, volumes and gap values were evaluated as function of molecular weights of salts by using the same level of theory. The AIM calculations show that the IFTB salt present the lower F---H distances in the two media. Evidently, the presence of a pyridine ring linked to C of C=O groups in IFTB favors the formation of halogen interaction, as compared with furyl and phenyl rings. NBO studies show that the higher delocalizations energies of halogen F---H interactions are observed in the Br-ITFB salt in both media together with the ITFB and Cl-ITFB salts. This study evidence clearly that the halogen F---H interaction play a important role in the reactivity and properties of trifluoroborate salts showing that the FTFB salt has lower volume, low corrected solvation energy and is the less reactive while the most reactive Br-ITFB, Cl-ITFB and IFTB salts present high stabilization energies of halogen F---H interactions and high corrected solvation energies. The analyses of the geometrical C-C, C-B, C=O, C-C-B, C-C-O and O-C-B parameters commons at all salts have showed notable influence on the halogen F---H interactions and on the properties of trifluoroborate salts